Workplace communication: are undergraduates ready to speak in English? - Tan, Bee Hoon (Academy of Language Studies, Universiti Teknologi MARA, 2012)
Since the inception of the Malaysian University English Test (MUET) in 1999, students seeking public university enrolment are encouraged to take the test. Up to now the public tertiary sector has not set a minimum MUET requirement officially, but faculties that offer competitive undergraduate programmes such as medicines have often indicated an entry MUET band of at least 3 or 4. While students’ English proficiency is somewhat gauged by the MUET upon university entry, their English proficiency is not systematically monitored or tested during the course of their tertiary education and upon graduating from their respective academic programmes. Although there is abundant anecdotal evidence in the mass media pointing to the general lack of communication skills especially in spoken English among graduates, there is little empirical research to inform stakeholders if undergraduates’ English competence is adequate for them to join the workforce upon graduation. Against this backdrop, the Test of Communication in English (TOCIE) was designed by the Department of English, Putra University of Malaysia (UPM), as a diagnostic or intervention mechanism so that proactive measures can be taken, if necessary, before university graduates start to work. This paper reports the salient results of UPM final-year undergraduates’ test performance on TOCIE over three semesters. Important findings and implications are also discussed.